2013
DOI: 10.1007/s10439-013-0858-7
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a 10-Year-Old Child Ligamentous Cervical Spine Finite Element Model

Abstract: Although a number of finite element (FE) adult cervical spine models have been developed to understand the injury mechanisms of the neck in automotive related crash scenarios, there have been fewer efforts to develop a child neck model. In this study, a 10-year-old ligamentous cervical spine FE model was developed for application in the improvement of pediatric safety related to motor vehicle crashes. The model geometry was obtained from medical scans and meshed using a multi-block approach. Appropriate proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…Compared to these two experimental values, the deviations in ultimate failure displacement were 8.6% and 25.5%, whereas deviations in ultimate failure force were 17.5% and 26.1%. We observed that failure occurred in the upper surface of the C3 endplate and the growth plate, similar to the locations predicted by Dong based on dynamic tensile simulations from a 10-year-old [15].…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Compared to these two experimental values, the deviations in ultimate failure displacement were 8.6% and 25.5%, whereas deviations in ultimate failure force were 17.5% and 26.1%. We observed that failure occurred in the upper surface of the C3 endplate and the growth plate, similar to the locations predicted by Dong based on dynamic tensile simulations from a 10-year-old [15].…”
Section: Resultssupporting
confidence: 85%
“…The pediatric cervical spine is significantly different from the adult spine with regard to its anatomical and material properties [2,10,15,31]. In this study, the C2-C7 cervical segmental response was first validated under the dynamic tensile response and the dynamic extension-flexion response were then compared with both segmental and global experimental data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The10-year-old pediatric ligamentous cervical spine model of head up to the T1 level was developed in a previous study (Dong et al 2013). The neck model, including muscles as shown in Figure 1, was created using the explicit FE solver LS-Dyna 971 (LSTC, Livermore, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Many phenomena can be described in terms of partial differential equations, and the finite element method (FEM) is a numerical approach with which these equations can be solved in approximate terms (Fish and Belytschko, 2009). In recent decades, computational studies using FEM have successfully analyzed biomechanical systems and have made important contributions to understanding the mechanical behavior of the human spine (Cheng et al, 2010;Dong et al, 2013;Fok et al, 2010;Ghista et al, 1988;Kakol et al, 2003;Lan et al, 2013;Lodygwski et al, 2005;Meijer et al, 2010;Rajasekaran et al, 2011;Teo and Ng, 2001;Travert et al, 2011;Tyndyk et al, 2007;Van Der Plaats et al, 2007;Wierszycki et al, 2006;Xia et al, 2003). Over time, different geometric models have been used, including everything from simple versions containing beam elements, represented by interconnected cylinders and bars (Ghista et al, 1988), to more comprehensive volumetric models of the spine.…”
Section: Introductionmentioning
confidence: 99%